Details of the Shikhara of the temple - Temples of India Project Team (Jio Institute, 2024)
Details of the shikhara (superstructure) of the temple along the western boundary of the Mahanaleshwar temple complex can be seen here. Though the temple is in ruins, the remains provide insight into the shekhari shikhara. Seen here is also the internal arrangement of stone blocks around the mulashringa (main aedicule).